Análisis del proceso de coproducción de la ordenanza de regulación del uso del espacio público para la comercialización de productos sanos en ferias agroecológicas del cantón Cayambe, Ecuador - López Robalino, Danny Joselito (2022)
This research analyzes the coproduction process of the Ordinance regulating the use of public space for the commercialization of healthy products in agroecological fairs, which was formulated in a participatory manner and launched since 2018 in the Cayambe canton. Said public policy is constituted as an example of how the State (local government) can intervene to promote the popular and solidarity economy sector, which the case studied corresponds to peasant agroecological production and solidarity marketing. The new public action based on a State-Society relationship is a real challenge since it facilitates the transition towards democratic governance, in this work it is sustained and legitimized in the historical, cultural, organizational and productive characteristics of these territory. In this aspect, the methodology used in the present study was qualitative, which allowed the deepening of the roles they play and the perceptions about compliance with the Ordinance by the state and non-state actors involved, where the institutionalization of the territorial community guarantee participatory system (SPG-CT) has a positive assessment, at the same time that some clues are given to improve the participatory implementation process, which until now has been partially developed.